Utilization of Epoxidized Palm Oil as A Plasticizer in Synthetic Leather - Andri Saputra; Ratri Retno Utami; Pani Satwikanitya; Muh. Wahyu Sya’bani; Dewi Nurhidayati; Luthfi Auliya Indahwati; Danuraja Ilmannafia (ASEAN Journal of Chemical Engineering, 2025)
Substituting petroleum-based plasticizers in the synthetic leather industry with renewable resources, such as epoxidized palm oil (EPO), will mitigate environmental pollution. This study aims to produce synthetic leather using EPO and compare its characteristics to those of synthetic leather using commercial plasticizers. Raw materials were compounded, coated on embossed paper, covered with reinforcing fabric, and cured in an oven at 180 oC for 1 minute. Control leather (CoL) was produced using diisononyl phthalate (DINP) and epoxidized soybean oil (ESBO), A leather (AL) was produced using DINP and EPO, B leather (BL) was produced only using EPO, and C leather (CL) was produced using EPO and ESBO. Synthetic leather was characterized for mechanical properties (SNI 1294:2009), glossiness (gloss meter), surface morphology (digital microscope), thermal properties (DSC), and functional groups (FTIR). The synthetic leather characteristics show that the thickness of AL and CL was close to CoL. The longitudinal tensile strength of BL (186.52 N) was not significantly different from CoL (191.41 N) and AL (190.06 N), whereas its transversal tensile strength (44.13 N) was not significantly different from CL (42.37 N). Both the longitudinal and transversal tear strengths of BL were not significantly different from those of AL. Furthermore, the glossiness of BL (4.37 GU) was not significantly different from CoL (4.22 GU) and AL (4.32 GU). Unlike CoL, EPO produces a smooth surface morphology (in AL, BL, CL) and eliminates pinhole defects. CoL, AL, BL, and CL exhibit similar functional groups. DSC analysis shows that BL exhibits thermal stability identical to CoL, AL, and CL. Our findings indicate that EPO could be a promising plasticizer for producing synthetic leather.